Natural products to control biofilm on painted surfaces - Bogdan, Sofia Tamara (2018)
This paper aims to study five vegetables extracts as possible additives to control bacterial growth on indoor water-borne paints. The extracts were obtained from the weeds Raphanus sativus, Rapistrum rugosum, Sinapis arvensis, Nicotiana longiflora and Dipsacus fullonum, used in traditional medicine as antimicrobial compounds.As a general rule, results showed that tested paints were efficient in inhibitingbiofilm formation, specially that formulated with Nicotiana longiflora.The tested paints can be used to protect walls from microbial colonizationwhich shortened coatings useful life by discoloration and/or degradation.Concomitantly, indoor microbial colonization by aerosols could be alsodiminished. This is especially important in places that should have highstandards of environmental hygiene as in the food industry, health-care andsanitary centers, etc.